Bifid Shape Is Intrinsic to Bifidobacterium adolescentis - Dhanashree,; Rajashekharan, Sharika; Krishnaswamy, Balamurugan; Kammara, Rajagopal (Frontiers in Microbiology, 2017)
Although the genus Bifidobacterium was originally named for its bifid morphology, not all bifidobacterial species have a similar structure, and very few of them adopt a bifid shape under stress conditions. The exposure of respective bifidobacterial species to various conditions, such as different pH, temperatures, medium components, in vivo growth in Caenorhabditis elegans, and subculture, did not affect their diverse morphologies. Extensive scanning electron microscopy studies suggested that the bifid shape of B. adolescentis are maintained irrespective of the conditions. Hence, we conclude that the bifid morphology is intrinsic to B. adolescentis. Most bifidobacterial species are anaerobic and rod-shaped, whereas, after the first generation, they become microaerophilic or aerophilic. CaCl2 (treatment of B. animalis) signaling triggered a change from the rod shape to the bifid shape and vice versa in B. adolescentis.